Prostatic Artery Embolization: A Systematic Review Article - Pooja Atkuri; Soumil Singhal; Mangerira Chinnappa Uthappa (The Arab Journal of Interventional Radiology)
Since the first case report in 2000, there has been a rapid expansion of prostatic artery embolization (PAE) as a therapy for symptomatic benign prostatic hyperplasia. The published literature and clinical experience show that this procedure is safe and effective. This article discusses the brief history, current issues in technique, and the state of the literature regarding outcomes of PAE. Current and future research topics are also discussed.